Sistemas inmutables de backup ante ataques de ransomware hacia una infraestructura TI - Cedeño Zambrano, José Reinaldo (2023)
Currently, cyber attacksare one of the main concerns of companies and even more ransomware threats of all kinds, government institutions, financial companies, health providers and others have been subject to this type of cybercrime, therefore, The objective of this research is to carry out a study and implementation of an immutable backup system using free software as a second line of defense against a computer attack that could compromise the technological infrastructure. The methodology used was quantitative and the execution method was a V cycle, the same one that integrates the phases of: specification, high-level and detailed design, implementation and phase of the unit, integration and operational test. As a result, an immutable backup of the data was made, which is a strategy and line of defense against ransomware, ensuring that the immutable backup is kept safe from disasters or cyber attacks. In conclusion, having at least three copies of the data immutable means that you should have at least two additional Backups in addition to the data in production, allowing that, if something happens with a Backup, there will be another one to which you can resort.